Sports Coaching and Youth Sports.A Case Study on How Good Practice in Sport England Funded Projects can be Monitored - Philippe Crisp (IPHO-Journal of Advance Research in Games and Sports, 2025)
In the UK responsibility for the public spend on community and youth sport is distributed through Sport England. The money received national is distributed at a sub-regional andthen local through their County Sport Partnership (CSP) system In this way various sport participation programmes, such as Sportivate and Satellite Clubs, are overseen by the County Sports Partnerships (CSP). Whilst all CSPs work in partnership with the Child Protectionin Sport Unit (CSPU) and will operate some form of service level agreement (including checks for insurance details andcriminal recordchecks have beencarried out for staffing), much of the work related to evaluations and safeguarding programmes is undertaken through self-reporting mechanisms. In light of this, Active Sussex (the Sussex CSP) sought to extend their quality assurance and welfare mechanisms by visiting a select number of their funded projects to check the robustness of various elements related to safeguarding. This paper presents the findings that resulted from over 30 site visits between April and July 2017. These findings suggest that the process of physically visiting some of the funded projects does,asexpected,allowfor a morethoroughaudit and proof ofcapability,butalsothatbest practice, in terms of coaching and overseeing youth and participation projects, can be shared.